Pengendalian Biaya Tenaga Kerja Langsung dalam Peningkatan Efisiensi Biaya Produksi - Wahyuningsih, Diah; Maulidiono, M Rifki (Jurnal Ilmiah Akuntansi Kesatuan, 2017)
Costs planning is a basic common issue faced by manufacturing companies where prior planned costs are being irrelevant with the actual costs, this especially happens with the case of labor costs. Companies must control costs effectively. Cost control can be measured by level of efficiency of previously budgeted cost and the real costs. Level of cost efficiency can be measured by comparing real costs with upcoming standard costs. This study aims to knowing how companies control its direct labor cost in order to increase production costs. The method applied in this study is qualitative descriptive analysis. The results show that when the company controls labor costs using methods such as finger print attendance to avoid cheating workers, standard procedures for operating machines, and faster production work standard of 51 days, we can conclude that the faster production the more efficient the costs spent by the company for the production process against the overhead costs consisted of water and electrical bills. On the other hand, we can also say that company’s policy towards the level of efficiency is 5%, mean while the actual level of efficiency is 0.43% for one unit production. This means that the cost control of direct labor costs run company still cannot achieve the expected level of efficiency.